Purchasing Power Parity Exchange Rates for the Global Poor - Deaton, Angus (2012)
The global poverty count uses a common global poverty line, often referred to as the dollar-a-day line, currently $1.25 at 2005 international prices, whose construction and application depends on purchasing power parity (PPP) exchange rates for consumption. The price indexes that underlie the PPPs used for this purpose are constructed for purposes of national income accounting, using weights that represent patterns of aggregate consumption, not the consumption patterns of the global poor. We use household surveys from 62 developing countries to calculate global poverty-weighted PPPs and to calculate global poverty lines and new global poverty counts.